2020
DOI: 10.21873/invivo.11990
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Nutritional Assessment Using the Controlling Nutritional Status Score to Predict Pancreatic Fistula After Pancreaticoduodenectomy

Abstract: Backgound: This study aimed to determine the usefulness of the Controlling Nutritional Status (CONUT) scorescore for predicting postoperative pancreatic fistula (POPF). Patients and Methods: Data from 108 consecutive pancreaticoduodenectomy cases performed at the Surgery Department of Iwakuni Clinical Center, from April 2008 to May 2018, were included. Preoperative patient data and postoperative complication data were collected. Results: Of the 108 patients (male=65; female=43; mean age=70 years), 41 (37.9%) h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 47 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…5. 9 Utsumi et al [35] (2020) Japan 2008.04-2018.09 Retrospective 108 32 5 Williamsson et al [36] (2020) Sweden 2010.01-2018.06 Retrospective 2503 245 1. 6.…”
Section: Blood Transfusionmentioning
confidence: 99%
“…5. 9 Utsumi et al [35] (2020) Japan 2008.04-2018.09 Retrospective 108 32 5 Williamsson et al [36] (2020) Sweden 2010.01-2018.06 Retrospective 2503 245 1. 6.…”
Section: Blood Transfusionmentioning
confidence: 99%
“…Utsumi et al [39] reported that the preoperative nutritional assessment using the Controlling Nutritional Status (CONUT) Score may predict the pancreatic fistula after PD. The CONUT score is a tool used to assess nutritional status.…”
Section: Immunomodulating Mechanisms Of Nutrients Used In Inmentioning
confidence: 99%
“…The authors concluded that patients with high CONUT scores were at high risk for POPF. According to them, preoperative immunonutrition might help reduce the POPF risk in these patients through modulating impaired immunity in them [39]. It regards the clinically relevant POPF classified as grade B and C, according to the International Study Group on Pancreatic Fistula classification [40].…”
Section: Immunomodulating Mechanisms Of Nutrients Used In Inmentioning
confidence: 99%
See 2 more Smart Citations